Translocator positron-emission tomography and magnetic resonance spectroscopic imaging of brain glial cell activation in multiple sclerosis. - Datta,G; Violante,IR; Scott,G; Zimmerman,K; Santos-Ribeiro,A; Rabiner,EA; Gunn,RN; Malik,O; Ciccarelli,O; Nicholas,R; Matthews,PM (Multiple Sclerosis, 2016)
BACKGROUND: Multiple sclerosis (MS) is characterised by a diffuse inflammatory response mediated by microglia and astrocytes. Brain translocator protein (TSPO) positron-emission tomography (PET) and [myo-inositol] magnetic resonance spectroscopy (MRS) were used together to assess this. OBJECTIVE: To explore the in vivo relationships between MRS and PET [(11)C]PBR28 in MS over a range of brain inflammatory burden. METHODS: A total of 23 patients were studied. TSPO PET imaging with [(11)C]PBR28, single voxel MRS and conventional magnetic resonance imaging (MRI) sequences were undertaken. Disability was assessed by Expanded Disability Status Scale (EDSS) and Multiple Sclerosis Functional Composite (MSFC). RESULTS: [(11)C]PBR28 uptake and [ myo-inositol] were not associated. When the whole cohort was stratified by higher [(11)C]PBR28 inflammatory burden, [ myo-inositol] was positively correlated to [(11)C]PBR28 uptake (Spearman's ρ = 0.685, p = 0.014). Moderate correlations were found between [(11)C]PBR28 uptake and both MRS creatine normalised N-acetyl aspartate (NAA) concentration and grey matter volume. MSFC was correlated with grey matter volume (ρ = 0.535, p = 0.009). There were no associations between other imaging or clinical measures. CONCLUSION: MRS [ myo-inositol] and PET [(11)C]PBR28 measure independent inflammatory processes which may be more commonly found together with more severe inflammatory disease. Microglial activation measured by [(11)C]PBR28 uptake was associated with loss of neuronal integrity and grey matter atrophy.